2021
DOI: 10.1016/j.esxm.2021.100415
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Cyst in Transgender Men: A Rare Complication Following Gender Affirming Surgery – A Case Series and Literature Overview

Abstract: Introduction Genital gender affirming surgery (gGAS) is usually the final stage in the medical transition for transgender men and consists of creating a neophallus and neo-scrotum, with or without urethral lengthening(UL). To reduce the complication risks of UL, a mandatory colpectomy is performed prior to UL. Colpectomy is considered a complex surgery, which may lead to various perioperative complications. There are few long-term complications reported. Aim To describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Our review revealed a lack of description of colpectomy complications, but there was high incidence (7.8% to 43.7%) of this finding in alternative cohorts of patients presenting for revision surgery. 14 Inconsistent language for similar findings may be the reason for this discrepancy, as the literature reported revisions for “perineal cyst,” 39 “persistent vaginal cavity,” 40 “fistula to native vagina,” 41 “diverticulum,” 42,43 and “mucocele.” 44 Vaginal remnant may have been used to refer to a space upon which full colpectomy was never performed, 45–47 whereas today, colpectomy is frequently advised in patients who wish to ultimately stand to void without device assistance. 48 Avoidance of this complication begins with complete, sharp excision of the vaginal mucosa using a transperineal, laparoscopic, or robotically assisted approach, and closure of the vaginal space with suture, 49 whereas some advocate for the use of an additional gracilis flap to further obliterate this space and buttress the urethral anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review revealed a lack of description of colpectomy complications, but there was high incidence (7.8% to 43.7%) of this finding in alternative cohorts of patients presenting for revision surgery. 14 Inconsistent language for similar findings may be the reason for this discrepancy, as the literature reported revisions for “perineal cyst,” 39 “persistent vaginal cavity,” 40 “fistula to native vagina,” 41 “diverticulum,” 42,43 and “mucocele.” 44 Vaginal remnant may have been used to refer to a space upon which full colpectomy was never performed, 45–47 whereas today, colpectomy is frequently advised in patients who wish to ultimately stand to void without device assistance. 48 Avoidance of this complication begins with complete, sharp excision of the vaginal mucosa using a transperineal, laparoscopic, or robotically assisted approach, and closure of the vaginal space with suture, 49 whereas some advocate for the use of an additional gracilis flap to further obliterate this space and buttress the urethral anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our review revealed a lack of description of colpectomy complications, but there was high incidence (7.8% to 43.7%) of this finding in alternative cohorts of patients presenting for revision surgery. 14 Inconsistent language for similar findings may be the reason for this discrepancy, as the literature reported revisions for "perineal cyst," 39 "persistent vaginal cavity," 40 "fistula to native vagina," 41 "diverticulum," 42,43 and "mucocele." 44 Vaginal remnant may have been used to refer to a space upon which full colpectomy was never performed, [45][46][47] whereas today, colpectomy is frequently advised in patients who wish to ultimately stand to void without device assistance.…”
Section: Specific To Phalloplasty and Metoidioplastymentioning
confidence: 99%
“…Sharp dissection of the vaginal epithelium in a submucosal plane is a precise matter to prevent nerve injury and bleeding from the perivaginal plexus (Asseler et al., 2021 ; Groenman et al., 2017 ; Nikkels et al., 2019 ). A treatment alternative with possibly less perivaginal tissue injury is colpectomy through electrothermal ablation, though (comparative) studies are lacking (Jun et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A treatment alternative with possibly less perivaginal tissue injury is colpectomy through electrothermal ablation, though (comparative) studies are lacking (Jun et al., 2021 ). It should also be mentioned that removal of the vaginal epithelium through electrothermal ablation may be less precise, leading to epithelial remnant with persistent vaginal discharge and the risk of perineal cysts (Asseler et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urethral diverticulae at the level of the perineal urethra may be asymptomatic if small, or if larger may lead to increase in post-void dribbling, pelvic pain, or recurrent infections (24). These should be distinguished from a persistent vaginal cavity or regrowth of the vaginal canal, which may present as prolonged and high-volume post-void dribbling, pelvic or perineal pain or fullness, "perineal cysts," and urinary tract infections (5,62). These remnants may communicate with the urethra, forming essentially a urethral diverticulum through the associated urethrovaginal fistula, or may not communicate with the urethra and be a mucocele.…”
Section: Urethral Diverticulae and Vaginal Regrowthmentioning
confidence: 99%